STUDY ON UPGRADED LOW RANK COALS PROPERTIES - Datin Fatia Umar; Bukin Daulay (Indonesian Mining Journal, 2009)
Upgraded brown coal (UBC) process has been discussed elsewhere. This process has been developed to produce an upgraded low rank coal with quality similar to a bituminous coal which is acceptable commer- cially and has low moisture content. Three Indonesian low rank coals, Berau, Tabang and Samaranggau coals were upgraded by upgraded brown coal (UBC) process to study the influence of the process on the properties of the upgraded low rank coals by conducting chemical and physical analyses such as proxi- mate, ultimate including calorific value and equilibrium moisture, functional group of C-H and C=O, coal petrography, specific surface area and briquettability. The result of proximate analysis indicated that the inherent moisture of the upgraded low rank coals de- creased significantly compared with that of the raw coals. Hence, the calorific value of the upgraded coals increased. The ash content of the upgraded coals was not change obviously due to that the UBC process was conducted at low temperature. However, the volatile matter content increased slightly due to the kero- sene or residue that left and pluged over coal pores to prevent the reabsorbtion of moisture. From ultimate analyses, carbon content of the upgraded coals increased, whereas the hydrogen and oxygen contents decreased. The UBC process hardly affected the sulfur and nitrogen contents. The result of equilibrium moisture measurement showed that the moisture content of all upgraded coals were less than 9%. The functional groups of C-H and C=O of the upgraded coals were slightly less than those of the raw coals. The aromaticity of the upgraded coals were increased. The petrography of both the raw and the upgraded coals indicated that the mean vitrinite reflectance was slightly higher in the upgraded coal compared to the raw coal. There was no significant quantity and textural differences of maceral in both coals. The specific surface area of the upgraded coals was lower than that of the raw coal due to the plugging of pore structure and shrinkage by residual oil addition. The upgraded low rank coals briquette according to drop shutter and compressive strength tests indicated good characteristics of briquette. Based on these results, UBC process only reduces the moisture content, so that the calorific value of the coal increases. Whereas the other parameters are not significantly change. UBC process does not increase the rank of the coal, therefore, it could only be applied to improve the calorific value of low rank coal which has low ash and sulfur contents.